Remediasi Tanah Tercemar Timbal di Lokasi Pertambangan Emas Selogiri, Wonogiri dengan Menggunakan Tuf Zeolitik - Aida, Lia Nazmi; Budianta, Wawan (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Soil contamination was commonly found in gold mining location in Selogiri, Wonogiri, and Central Java and need serious attention for remediation action. This study aimed to investigate the mineralogical characteristic of zeolitic tuff and to analyze the influence of its characteristic for lead sorption on soil in mining, as mentioned earlier location. The soil sample was obtained from around the gold mining location. The zeolitic tuff was obtained in two locations in Gunungkidul, Yogyakarta: A and B. Zeolitic tuff samples were then characterized for mineralogy content using polarization microscopes, cation exchange capacity (CEC) by using barium chloride method and XRD (X-Ray Diffraction) analysis. A batch test was conducted on a laboratory scale by shaking zeolitic tuff samples with soil samples in a CaCl2 solution. The solution was then shaken using a magnetic stirrer, and the filtrate was sampled at a specific time interval. The batch test result showed that the zeolite mineral percentage influenced the sorption behavior of zeolitic tuff in the sample and the value of CEC, which the more zeolite mineral and CEC value, the higher of sorption capacity achieved up to 58.8%. Hence, zeolitic tuff investigated in this study has a promising material for the remediation of Pb-contaminated soil in Selogiri, Wonogiri, and Central Java.